In Situ Dendritic Cell Recruitment and T Cell Activation for Cancer Immunotherapy - Han, Joonsu; Bhatta, Rimsha; Liu, Yusheng; Bo, Yang; Wang, Hua (Frontiers in Pharmacology, 2022)
Cancer immunotherapy has shifted the paradigm for cancer treatment in the past decade, but new immunotherapies enabling the effective treatment of solid tumors are still greatly demanded. Here we report a pore-forming hydrogel-based immunotherapy that enables simultaneous recruitment of dendritic cells and in situ activation of T cells, for reshaping the immunosuppressive tumor microenvironment and amplifying cytotoxic T lymphocyte response. The injectable pore-forming hydrogel composed of porogen-dispersed alginate network can form a macroporous structure upon injection into mice, and enables controlled release of granulocyte-macrophage colony-stimulating factor (GM-CSF), a chemoattractant for recruiting dendritic cells, and epacadostat, an inhibitor of indoleamine 2,3-dioxygenase for activating T cells. We show that gels loaded with GM-CSF and epacadostat, after peritumoral injection, can recruit massive dendritic cells in situ and activate effector T cells in the tumor tissues, resulting in enhanced frequency and activation status of dendritic cells, reduced numbers of regulatory T (Treg) cells, and increased CD8+/Treg ratios in the tumor microenvironment. This hydrogel-based immunotherapy holds great promise for treating poorly-immunogenic solid tumors.